MRA of the Supraaortic Vasculature: Comparison of Gadobutrol and Gadoterate Meglumine at 1.5 T. Issue 2 (25th December 2021) - Cerne, John W.; Pathrose, Ashitha; Singer, Alyssa M.; Moore, Jackson E.; Serhal, Ali; Aouad, Pascale; Umair, Muhammad; Ragin, Ann; Allen, Bradley D.; Avery, Ryan; Markl, Michael; Carr, James C.
Abstract : Background: Gadobutrol (GB) and gadoterate meglumine (GM) are contrast agents used for contrast‐enhanced magnetic resonance angiography (CEMRA). Supraaortic vasculature (SAV) CEMRAs are used to evaluate stroke risk and neurologic symptoms. There is a need to compare the SAV CEMRA image quality obtained with GB and GM. Purpose: To intra‐individually compare MRA images obtained with equimolar GB and GM at 1.5 T in the SAV. Study Type: Prospective, crossover. Population: Twenty‐eight subjects (54 ± 13 years; 17 female). Field Strength/Sequence: 1.5 T; three‐dimensional (3D) gradient recalled echo. Assessment: Quantitative image quality was measured by normalized signal intensity (SIn ) [SIn = SI blood/SD blood] and contrast ratio (CR) [CR = SI blood/SI muscle], determined by an observer (JWC) with 1 year of vascular imaging experience. Three radiologists (AS, PA, and MU) with (5, 5, and 6 years of) vascular imaging experience evaluated image quality by Likert‐scale ratings (of image impression, wall conspicuity, and artifact absence). Statistical Tests: SIn and CR were compared with paired t ‐tests or Wilcoxon signed‐rank tests and Bland–Altman plots. Qualitative ratings were compared with Wilcoxon signed‐rank test. Results: No significant difference in SIn was found between GB and GM. CRs with GB were significantly higher than GM at the right common carotid (6.9 ± 2.5 vs. 4.8 ± 1), left internal carotid (7.3 ± 2 vs. 4.4 ± 1.2), right internal carotid (7.7 ± 2.2 vs. 5 ± 1.1), and left vertebral (6.6 ± 2.2 vs. 4.5 ± 1.1) arteries. Bland–Altman plots showed relatively greater differences between GB and GM at higher CRs and SIn s. GM showed significantly higher artifact than GB (3.56 ± 0.52 vs. 3.36 ± 0.46) and significantly lower overall image quality (10.73 ± 1.45 vs. 11.26 ± 1.58) at the left vertebral artery. Data Conclusion: At 1.5 T and equimolar demonstration, GB (0.1 mL/kg, i.e., 0.1 mmol/kg) showed higher CRs in the SAV compared to GM (0.2 mL/kg, i.e., 0.1 mmol/kg) at most vessels. Subjective image quality was not significantly different between the two agents for most vessels. Level of Evidence: 2 Technical Efficacy: Stage 2